The emergency department triage of community-acquired pneumonia project data and documentation systems a model for multicenter clinical trials. - Obrosky, D.S (IEEE Transactions on information technology in biomedicine)
Multicenter clinical trials are complex undertakings that require significant resources to ensure efficient, high quality research. This paper describes the goals, design, and implementation of a multicenter clinical trial database management system to support this aim. A large number of study sites or patients, and the goal of automatically generating large portions of data management infrastructure from common metadata, motivated the development of the system. This paper also describes extensions for a generalized project documentation system, and discusses plans for further extensions and improvements based on observed strengths, limitations, and anticipated technological change